Factors Associated with Retention in Care One Year after Deliveryin Patients Undergoing Prevention of Mother to Child Transmission(PMTCT) at RSCM - Yulidar, Yulidar; Yunihastuti, Evy; Djauzi, Samsuridjal; Padmita, Astrid Citra; Koesnoe, Sukamto (UI Scholars Hub, 2017)
Introduction. Retention in care is important to the successful of HIV treatment. This study is aimed to analyze factors associated with retention in care one year after delivery in patients undergoing PMTCT at HIV integrated clinic of RSCM. Methods. A retrospective cohort study was conducted among post-partum HIV patients who were given ARV therapy for PMTCT at HIV intergrated clinic of Cipto Mangunkusumo Hospital from January 2004 to May 2014. Evaluation of one year retention in care after PMTCT was performed by observing medical records of the patient. The collected data were factors associated with one year after delivery retention in care including age of patients, level of initial CD4, ARV toxicity, injecting drug user, duration of ARV before delivery, having child with positive HIV status, having spouse with positive HIV status, distance from the residence to the hospital, and indication of ARV. Bivariate analysis was performed by using Chi Square and Mann Whitney test and multivariate anaysis was performed by using logistic regression to assess factors associated with retention in car after PMTCT program. Results. 253 subjects met the inclusion criteria. In One year after delivery, the retention in care rate was 55,3%. Multivariate analysis found that factors significantly associated with one year retention in care were indication of ARV initiation for therapy (OR =3,812 [95% CI: 1,825-7,966]), non-IDU patients (OR=3,055 [95% CI: 1,382-6,752]), duration of ARV before delivery for more than 6 months (OR = 2,657 [95% CI: 1,328-5,316]), and level of initial CD4 less than 200/mm3 (OR = 2,033 [95% CI: 1,061-3,894]). Conclusions. Factors significantly associated with one year after delivery retention in care are indication of ARV for therapy, duration of ARV before delivery, non-IDU patients, and level of initial CD4 less than 200/mm3 . and Mann Whitney test and multivariate anaysis was performed by using logistic regression to assess factors associated with retention in car after PMTCT program. Results. 253 subjects met the inclusion criteria. In One year after delivery, the retention in care rate was 55,3%. Multivariate analysis found that factors significantly associated with one year retention in care were indication of ARV initiation for therapy (OR =3,812 [95% CI: 1,825-7,966]), non-IDU patients (OR=3,055 [95% CI: 1,382-6,752]), duration of ARV before delivery for more than 6 months (OR = 2,657 [95% CI: 1,328-5,316]), and level of initial CD4 less than 200/mm3 (OR = 2,033 [95% CI: 1,061-3,894]). Conclusions. Factors significantly associated with one year after delivery retention in care are indication of ARV for therapy, duration of ARV before delivery, non-IDU patients, and level of initial CD4 less than 200/mm3 .